2018
DOI: 10.1142/s0217732318500244
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous leptonic U(1) symmetry: Syndetic origin of the QCD axion, weak-scale dark matter, and radiative neutrino mass

Abstract: The well-known leptonic U(1) symmetry of the standard model of quarks and leptons is extended to include a number of new fermions and scalars. The resulting theory has an invisible QCD axion (thereby solving the strong CP problem), a candidate for weak-scale dark matter, as well as radiative neutrino masses. A possible key connection is a color-triplet scalar, which may be produced and detected at the Large Hadron Collider.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…These include colored versions of the model [8][9][10][11] and versions with additional states and/or symmetries, both in Dirac [12][13][14][15][16][17][18][19][20] and Majorana fashion . The Z 2 parity can also be promoted to a local [66,67] or global U(1) symmetry [68][69][70][71], or to a Peccei-Quinn quasi-symmetry [72][73][74]. Finally, Scotogenic-like scenarios have also been combined with, or even obtained from, extended gauge symmetries [75][76][77][78].…”
Section: Jhep07(2020)097mentioning
confidence: 99%
“…These include colored versions of the model [8][9][10][11] and versions with additional states and/or symmetries, both in Dirac [12][13][14][15][16][17][18][19][20] and Majorana fashion . The Z 2 parity can also be promoted to a local [66,67] or global U(1) symmetry [68][69][70][71], or to a Peccei-Quinn quasi-symmetry [72][73][74]. Finally, Scotogenic-like scenarios have also been combined with, or even obtained from, extended gauge symmetries [75][76][77][78].…”
Section: Jhep07(2020)097mentioning
confidence: 99%
“…GeV. Other studies on the link between U(1) PQ symmetry and neutrino/flavour can be found in [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: The Axion and The Dirac Neutrinomentioning
confidence: 99%
“…In [20] the Dirac neutrino masses were generated through a type-I Dirac seesaw. Scenarios where the neutrino mass mechanism and the PQ symmetry breaking are related has attracted attention 1 , both in the Majorana [23][24][25][26][27][28][29] and Dirac [30][31][32][33] frameworks.…”
Section: Introductionmentioning
confidence: 99%